2016
DOI: 10.1148/radiol.2016151951
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumors: The Influence of Tumor Type and Routine MR Imaging Characteristics at BOLD Functional MR Imaging in the Primary Motor Gyrus

Abstract: Purpose:To evaluate the effects of histologic features and anatomic magnetic resonance (MR) imaging characteristics of brain tumors on the functional MR imaging signal in the primary motor cortex (PMC), as false-negative blood oxygen leveldependent (BOLD) functional MR imaging activation can limit the accurate localization of eloquent cortices. Materials andMethods:Institutional review board approval was obtained, and informed consent was waived for this HIPAA-compliant retrospective study. Conclusion:BOLD fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…A previous study verified that gliomas caused a decline in BOLD fMRI activation by neurovascular uncoupling when the glioma was near the primary motor cortex. 40 Our results were consistent with this theory to some extent. However, another study suggested that the distance between the tumor and primary motor cortex was no more likely than tumor type in influencing BOLD fMRI activation.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study verified that gliomas caused a decline in BOLD fMRI activation by neurovascular uncoupling when the glioma was near the primary motor cortex. 40 Our results were consistent with this theory to some extent. However, another study suggested that the distance between the tumor and primary motor cortex was no more likely than tumor type in influencing BOLD fMRI activation.…”
Section: Discussionsupporting
confidence: 90%
“…This effect is due to affected neovasculature and the presumable uncoupling of the neurovascular response, effects to which patients with HGG are particularly susceptible. 1,13,17 In this context, it has recently been demonstrated that nTMS-based DTI FT, as applied in this study, can overcome the limitations of manual ROI seeding by relying on neurophysiological functional parameters that should not be severely distorted by changed oxygenation levels. 10,15,19,37 Addition- Summary of the findings concerning lesion-to-CST distances, which were compared among patients with HGG regarding the presence of tumor-related edema (no edema/edema).…”
Section: Association Between Ntms and Clinical Outcomementioning
confidence: 98%
“…Concerning fMRI, it has been demonstrated that the blood oxygenation level-dependent (BOLD) contrast lacks accuracy in patients with changed intracranial oxygen levels, which are regularly present in the vicinity of gliomas due to their glucose and oxygen consumption from surrounding brain tissue. 13,15,22,51 In contrast to BOLD fMRI, preoperative MEG in patients harboring brain tumors is not reported to severely suffer from altered oxygen levels. However, MEG represents a more expensive alternative that is not widely available.…”
Section: Discussion Preoperative Language Mappingmentioning
confidence: 99%